Chemical recycling of waste poly-p-phenylene terephthamide via selective cleavage of amide bonds catalyzed by strong Brönsted base in alcohols. (1st January 2022) - Tian, Zishang; Shao, Xiaojie; Zhang, Jiaojiao; Su, Lijuan; Wang, Yingxiong; Deng, Tiansheng; Wang, Yuqi; Hou, Xianglin
Graphical abstract: Highlights: PPTA was completely degraded in 5 wt% NaOH/ n -butanol system at 180 °C for 6 h. The yields of TPA and PPD were up to 92.0% and 91.5%, respectively. The wettability of n -alcohols on PPTA had obvious effect on PPTA degradation. The addition of a small amount of water can accelerate the degradation of PPTA. Abstract: Poly-p-phenylene terephthamide (PPTA) is widely applied in bulletproof products and composite materials because of its high strength, high modulus, high temperature resistance and creep resistance. The PPTA molecule with highly symmetrical and regular structure is linear structure formed by the alternating connection of benzene ring and amide bond, and the amide bonds between the molecular chains form strong hydrogen bonds. Therefore, the dissolution and depolymerization of PPTA is very challenging. In this work, an efficient catalytic system was developed for the controllable degradation of waste PPTA, and the high-value added monomers terephthalic acid (TPA) and p-phenylenediamine (PPD) were recovered. The results show that the amide bonds of PPTA can be selectively cleaved by the strong Brönsted base catalysts in alcohols, especially in the NaOH/ n -butanol system. Under the optimal degradation conditions (5 wt% NaOH in n -butanol, 180 °C, 6 h), the percentage degradation of PPTA is 100%, and the yields of TPA and PPD are 92.0% and 91.5%, respectively. In addition, it is found that the wettability of n -alcohols on PPTA monofilament and the addition of a small amount of water have important influences on the degradation of PPTA. The work elucidates the degradation mechanism of PPTA, and reveals the important factors affecting the depolymerization of PPTA.